Life cycle assessment of pyrolysis process of Desmodesmus sp. - Gang, Li; Fang, Ji; Yuguang, Zhou; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2015)
This paper described a comprehensive assessment of the pyrolysis process of 1 kg Desmodesmus sp. cultivated in BG11 medium at the optimum temperature by using life cycle assessment method. This assessment took 1 kg of Desmodesmus sp. as a functional unit, and chose energy efficiency analysis and potential environmental impact as assessment indices. The results showed that the energy conversion efficiency index of the pyrolysis process was above 1, which meant the pyrolysis process was beneficial. The primary impact of the pyrolysis process on the environment was eutrophication; which followed by photochemical ozone synthesis and acidification; and global warming impact was the last. The overall environmental impact during the whole life cycle was 1 347.63 mPET2000.Keywords: life cycle assessment (LCA), microalgae, pyrolysis, energy conversion efficiency, environmental impactDOI: 10.3965/j.ijabe.20150805.2069Citation: Li G, Ji F, Zhou Y G, Dong R J. Life cycle assessment of pyrolysis process of Desmodesmus sp. Int J Agric & Biol Eng, 2015; 8(5): 105－112.